Pengaruh Iklan Shopee terhadap Keputusan Pembelian di Toko Obayito Group - Amalia, Devi; Dherem, Ishom Muhammad (LPPM STT Terpadu Nurul Fikri, 2024)
This journal discusses the influence of Shopee Ads on purchase decisions at the Obayito Group Store. As a digital advertising service provided by Shopee, Shopee Ads enables sellers to promote their products to potential buyers. The research employs a quantitative method with secondary data analysis based on the sales data of the Obayito Group Store before and after the implementation of Shopee Ads. This study shows that Shopee Ads positively and significantly impact purchasing decisions, consumer trust, and consumer loyalty at Obayito Group Stores. Data analysis shows that consumers exposed to Shopee Ads are more likely to make purchases, have a higher level of trust in the store, and tend to remain loyal to shop at Obayito Group Stores. The evaluation results show that Shopee Ads effectively increase sales, which is essential in building store credibility and reputation and improving customer loyalty. The implications of this study provide practical suggestions for Obayito Group Stores to optimize Shopee Ads advertising campaigns. At the same time, Shopee can continue to improve its ads platform to provide better services to sellers. As such, Shopee Ads emerges as a strategic marketing tool to achieve the marketing obje ctives of Obayito Group Stores.